Landscapes in the Eastern Mediterranean between the Future and the Past - Vogiatzakis, Ioannis N. (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Landscapes have long been viewed as 'multifunctional', integrating ecological, economic, sociocultural, historical, and aesthetic dimensions. Landscape science and public awareness in Europe have been progressing in leaps and bounds. The challenges involved in landscape-related issues and fields, however, are multiple and refer to landscape stewardship and protection, as well as to the development of comprehensive theoretical and methodological approaches, in tandem with public sensitization and participatory governance and in coordination with appropriate top-down planning and policy instruments. Landscape-scale approaches are fundamental to the understanding of past and present cultural evolution, and are now considered to be an appropriate spatial framework for the analysis of sustainability. Methods and tools of landscape analysis and intervention have also gone a long way since their early development in Europe and the United States. Although significant progress has been made, there remain many issues which are understudied or not investigated at all-at least in a Mediterranean context. This Special Issue addresses the application of landscape theory and practice in the Eastern Mediterranean and mainly, but not exclusively, reports on the outcomes of an international conference held in Jordan, in December 2015, with the title "Landscapes of Eastern Mediterranean: Challenges, Opportunities, Prospects and Accomplishments". The focus of this Special Issue, landscapes of the Eastern Mediterranean region, thus constitutes a timely area of research interest, not only because these landscapes have so far been understudied, but also as a rich site of strikingly variegated, long-standing multicultural human-environmental interactions. These interactions, resting on and taking shape through millennia of continuity in tradition, have been striving to adapt to technological advances, while currently juggling with manifold and multilayered socioeconomic and climate-environmental crises.